Achieving American Diabetes Association goals in HIV-seropositive patients with diabetes mellitus - Bury, John E. (Baylor Health Care System, 2007)
This retrospective study examined whether the goals set forth by the American Diabetes Association were being attained in an HIV specialty clinic run by internal medicine physicians. The charts of 40 HIV patients with diabetes were reviewed. Patients were divided into two groups: those who had seen a clinical pharmacist for medication adherence counseling (n = 20) and those who had not (n = 20). Overall, less than 50% of patients were achieving goals of therapy for hemoglobin A(1c), cholesterol, triglycerides, and blood pressure. Only 5% were documented as receiving aspirin therapy. The medication adherence counseling was not a significant factor in the results. Clinicians need to be aware of the concomitant disease states that HIV patients have and to treat those disease states to the standard of care set forward.